Asperger syndrome and the supposed obligation not to bring disabled lives into the world. Issue 9 (31st July 2010) - Walsh, Pat
Abstract : Asperger syndrome (AS) is an autistic spectrum condition that shares the range of social impairments associated with classic autism widely regarded as disabling, while also often giving rise to high levels of ability in areas such as maths, science, engineering and music. The nature of this striking duality of disability and ability is examined, along with its implications for our thinking about disability and the relevance of levels and kinds of disability to reproductive choices. In particular, it may be seen as posing a challenge to John Harris's influential position in reproductive ethics relating to disability. The paper argues that if, as Harris maintains, there is a quite general moral obligation to avoid bringing disabled lives into the world regardless of the level of disability, then AS must be seen as having a strong claim to be exempt from such an obligation. However, a broader critique of Harris's position leads to the conclusion that, in fact, this putative obligation does not exist.